Short Communication: Dextran production using Leuconostoc mesenteroides strains isolated from Borassus flabellifer sap (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ma'unatin A, Harijono, Zubaidah E, Rifa'i M. 2022. Short Communication: Dextran production using Leuconostoc mesenteroides strains isolated from Borassus flabellifer sap. Biodiversitas 23: 1154-1158. Exopolysaccharide (EPS) is a carbohydrate polymer secreted by several bacteria in their growth period, including Lactic Acid Bacteria (LAB). Dextran is a type of EPS produced by Leuconostoc mesenteroides and is used widely in the food and pharmaceutical fields. Therefore, this study aimed to evaluate the potency of two strains of L. mesenteroides isolated from Borassus flabellifer L. (lontar) sap, namely L. mesenteroides N5 and N7 for dextran production using the MRS broth medium supplemented with sucrose at varying concentrations of 5, 10, and 15% (w/v). The results showed that L. mesenteroides N5 produced dextran of 14.53 g/L in medium with 15% sucrose, while L. mesenteroides N7 yielded 13.16 g/L at 10% sucrose. The characteristics of selected dextran showed that it contains 89.93% total carbohydrate, 2.33% protein and has a surface structure with tight pore for dextran N5 while the dextran N7 contains 87.84% total carbohydrates, 2.22% protein and has looser porous surface structure.
Keywords: Dextran, exopolysaccharide, Leuconostoc mesenteroides, sucrose